Whole-Genome Sequence and Interaction Analysis in the Production of Six Enzymes From the Three Bacillus Strains Present in a Commercial Direct-Fed Microbial (Norum™) Using a Bliss Independence Test - Hernandez-Patlan, Daniel; Solis-Cruz, Bruno; Latorre, Juan D.; Merino-Guzman, Ruben; Morales Rodríguez, Miguel; Ausland, Catie; Hernandez-Velasco, Xochitl; Ortiz Holguin, Oscar; Delgado, Ramiro; Hargis, Billy M.; Singh, Pallavi; Tellez-Isaias, Guillermo (Frontiers in Veterinary Science, 2022)
Norum™ (Eco-Bio/Euxxis Bioscience LLC) is a Bacillus spore direct-fed microbial (DFM). The Bacillus isolates were screened and selected based on in vitro enzyme production profiles. Moreover, in chickens fed high non-starch polysaccharides, this DFM demonstrated to reduce digesta viscosity, bacterial translocation, increase performance, bone mineralization, and balance the intestinal microbiota. In the present study, we present the whole genome sequence of each of the three isolates in Norum™, as well as the synergistic, additive, or antagonistic effects on the enzyme production behavior of three Bacillus strains and their combinations when grown together versus when grown individually. Whole genome sequence identified isolate AM1002 as Bacillus subtilis (isolate 1), isolate AM0938 as Bacillus amyloliquefaciens (isolate 2), and isolate JD17 as Bacillus licheniformis (isolate 3). The three Bacillus isolates used in the present study produce different enzymes (xylanase, cellulase, phytase, lipase, protease, and β-glucanase). However, this production was modified when two or more Bacillus strains were combined, suggesting possible synergistic, antagonistic, or additive interactions. The Bliss analysis suggested (P < 0.05) that the combination of Bacillus strains 1-2 and 1-2-3 had intermediate effects and predicted that the combination of Bacillus strains 2-3 could have better effects than the combination of all the 3 Bacillus strains. In summary, the current study demonstrated the need of selecting Bacillus strains based on quantitative enzyme determination and data analysis to assess the impacts of combinations to avoid antagonistic interactions that could limit treatment efficacy. These results suggest that using Bacillus strains 2-3 together could lead to a new generation of DFM's with effects superior to those already examined in Bacillus strains 1-2-3, and therefore a potential alternative to growth-promoting antibiotics. More research utilizing poultry models is being considered to confirm and expand the existing findings.